Fredric Jameson
XXII, 242 p.
Keywords: This volume brings together original work from internationally recognized scholars that critically engages with the full range of Jameson's work, including: Sartre, Lukács, 'Third World' literature, architecture, postmodernity, globalization, film, dialectics and Brecht. In a series of lively, and at times iconoclastic readings, the contributors challenge accepted views of Jameson's work and locate his project in the historical, political and institutional context that shaped it. The volume concludes with an original contribution by Jameson himself, providing an opportunity for readers to critically engage with his work themselves.